SMALL AND MEDIUM SCALE BUSINESS FAILURE IN NIGERIA - Alo, Olubunmi Akinsanya; Olatunji, Kareem Alidu (IJRDO - Journal of Social Science and Humanities Research, 2018)
The developed and developing nations of the world are facing high rate of failures among small and medium scale enterprises (SMESs). The experience of Nigeria is very pathetic as many of these businesses fail too often and many die in their infancy. Given the high failure rate of small and medium scale enterprises internationally and locally, the objectives of this study are; to investigate the cases of failure among SMESs in Nigeria, to determine the influences of socio cultural factors on small and medium scale business failure in Nigeria and to ascertain measures that can ameliorate the failure rate of these businesses. Qualitative method is adopted in this study through in-depth interview of owner-manager of fifty purposively selected SMESs and observation of their transaction records, and the expansion of their workforce (employees) in the last three years. Findings show that most of the small scale enterprises failed due to lack of infrastructural facilities and entrepreneurial skills, inadequate managerial skills, illiteracy, obsolete technology, insufficient finance, multiple taxations by different levels of government, neglect, fraud, corruption and natural disaster. Socio-cultural factors impacting negatively on business failure are attitude, norms, values, religious belief and ostentatious life style of citizen. This study recommended adequate business planning, strategic implementation of procedures, training of owner-manager to acquire entrepreneurial skill, reduction of interest rates by financial institutions, provision of infrastructural facilities and human capital development. If these measures are put in place SMESs will be able to play their role in the area of employment generation, wealth creation, increasing standard of living of the citizenry and generate foreign exchange for the country to boast her Gross National Products and consequently achieve economic growth and sustainable development.